Andreï Makine, témoin intemporel de la guerre en Russie soviétique - Alexia Gassin (Carnets)
In his works, the French writer of Russian origin Andreï Makine repeatedly deals with the topic of war. He crosses the boundaries of time to evoke the Russian civil war as well as the two world wars. Although the author did not live through these conflicts, he describes them in a very realistic way, drawing the most horrific pictures with the objectivity of a war columnist. Indeed, according to Makine novels are a “fictionalized idea”, an idea “based on knowledge, on a testimony”. As a result, we can assume that Makine spoke with several people who had experienced war and/or undertook a thorough search of the archives (of museums) with the purpose of retranscribing the information found in his novels and of giving voice to the human being. He therefore opposes the propaganda found in memoirs and textbooks, and favours individual history over great world History.